Analisis instrumen penilaian kurikulum 2013 buku guru kelas V tema 8 edisi revisi 2017 berdasarkan perspektif HOTS sebagai transfer of knowledge - Fajar Kurniawan; Retno Winarni; Anesa Surya (Didaktika Dwija Indria, 2021)
The purpose of this study is to determine the assessment instrument based on HOTS perspective (Higher Order Thinking Skills) in the thematic book of the fifth grade teacher theme 8 "our friend's environment". This research is a qualitative descriptive research with content analysis method. The data source of this research is the thematic book of the fifth grade teacher theme 8 "our friend's environment" which contains KI, KD, learning objectives, learning steps, student activities and learning assessment grids. The sampling technique used purposive sampling technique with the semantic data validity test technique. The data analysis technique uses the Milles and Hubberman model technique through four stages which include data collection, data reduction, data display and conclusion drawing. The results obtained are that there is an assessment rubric in accordance with the HOTS (Higher Order Thinking Skills) perspective.